A first inventory of gypsum flora in the Palearctic and Australia - Pérez-García, Francisco J.; Akhani, Hossein; Parsons, Robert F.; Silcock, Jennifer L.; Kurt, Latif; Özdeniz, Ebru; Spampinato, Giovanni; Musarella, Carmelo M.; Salmerón-Sánchez, Esteban; Sola, Fernando; Merlo, María E.; Martínez-Hernández, Fabián; et al. (Mediterranean Botany, 2018)
Gypseous substrates are well-recognised as supporting distinctive and unique flora assemblages, including numerous gypsum endemic (gypsophile) species. Along with these, others are also frequent although their presence is not restricted to gypsum; they show a clear preference for them (gypsocline). While this phenomenon (gypsophily) has been studied regionally, and various hypotheses put forward to explain it, there has been little global synthesis. We present a preliminary check-list on the gypsophile and gypsocline flora of the Palaearctic and Australian areas as a part of a project to develop a global checklist of the World’s gypsophytes, which can broaden our ecological and biogeographical understanding of these unique environments. The database contains 935 taxa spanning 54 countries. The Irano-Turanian region —and to a lesser extent the Mediterranean region— emerged as the richest territories in terms of gypsophile species; this richness was much reduced in the Saharo-Arabian and, especially in the Eurosiberian regions. The factors that can modulate the richness of gypsophytes in a region are discussed and have been distributed into four groups: a) geological and edaphic factors; b) factors linked to the insular nature of outcrops; c) climatic variables and their interaction with the soil; d) biogeographical factors. The importance of those factors linked to insularity and, especially, to water availability is emphasized. Because the soil structure of many gypsum outcrops reduces water ability to plants, such outcrops can be regarded as “dry-islands” surrounded by less xeric substrates. The fact that gypsophytes can be grouped within a few major flowering plant clades across continents, confirms their pre-adaptations to these harsh and unique environments. Our work provides a preliminary database for exploring ecological and biogeographic issues relating to gypsophily, and we hope it will stimulate global interest in these valuable ecosystems.